THE IMPACT OF GEOMORPHOLOGY, CLIMATE AND LAND-USE CHANGE ON THE 2014 – 2015 FLOODING EVENTS IN KELANTAN, MALAYSIA - ISMAIL, NUR AFIQAH (2019)
Floods are natural phenomenon. In Kelantan which commonly experience river flooding during the monsoon months of October – January. However, the 2014 Kelantan floods were the worst on records in terms of depth and extent of inundation as well as damages to properties and infrastructure. Many villages in upstream areas were totally under water whilst new localities in downstream areas were added to the list of flood prone areas. Geomorphologically and hydrologically, the 2014-2015 Kelantan flood comprised two (2) distinct but inter-connected floods. These are referred to as the: - i) Upstream highland flood, and ii) Lowland Kelantan delta flood.